Employment and income effects of improved cook stove and pico-solar interventions: An impact evaluation of the EnDev Kenya Programme - Gunther Bensch; Nicolas Jersch; Jochen Kluve; Jonathan Stöterau (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
[Background] This report presents results of an impact evaluation of a market-based energy access intervention implemented by the Energising Development (EnDev) programme in rural Kenya. The EnDev Kenya intervention seeks to establish and enhance self-sustaining markets for modern energy technologies in rural areas by training and mentoring individuals on how to run small businesses in improved cook stoves or pico-solar technologies. The EnDev Kenya programme was established in 2006 and is composed of three core components: improved cook stoves, pico-solar and biogas. This report focuses on the first two components. Both are implemented by GIZ in cooperation with SNV who currently operate in 21 of the 47 counties in Kenya. The improved cook stoves component promotes the sustainable production, marketing, installation and use of the so-called `Jiko Kisasa Stoves' and `Rocket Stoves'. According to the EnDev monitoring system, over 1.9 million improved cook stoves are in use by mid-2015, effectively reaching over 4.5 million people. The solar component was launched in 2012 and promotes the use of small solar lighting systems that have been quality approved by the Lighting Africa Initiative. Up to June 2015, over 120,000 pico-PV lanterns have been sold by entrepreneurs cooperating with the programme. Both components follow a market-based approach: Prospective entrepreneurs are mobilized in local communities and trained in technological, business and marketing skills related to either of these technologies. Following the training, active entrepreneurs gather at regular local meetings to report their sales figures to the local EnDev coordinator. These meetings also serve as a basis for exchange with the programme and other entrepreneurs, as well as the promotion of further training opportunities by EnDev. In addition, EnDev Kenya also performs a range of related activities in the target areas such as awareness creation, promotional activities, and consumer education. [...] – – Diese Evaluierung befasst sich mit der zentralen Forschungsfrage, inwieweit die EnDev-Maßnahme in Kenia zu einer Verbesserung der Beschäftigungs- und Einkommenssituation unter den geförderten Kleinstunternehmern geführt hat. In den untersuchten ländlichen Gebieten wird Einkommen in der Regel aus unterschiedlichen, eher unberechenbaren Quellen bezogen. Vor diesem Hintergrund wird untersucht, ob die geförderten Kleinstunternehmer andere Einkommen schaffende Maßnahmen zugunsten des Solar- oder Herdgewerbes zurückfahren oder aufgeben, oder ob es alternativ zu einer Verstetigung und Diversifizierung von Einkommensquellen kommt. In dem Zusammenhang untersucht die Studie insbesondere, ob die von EnDev geförderte Existenzgründung die Abhängigkeit von der Landwirtschaft mindert. Verschiedene objektive und subjektive Indikatoren zu Beschäftigung, Einkommen und Wohlbefinden werden analysiert. Schließlich wird erforscht, inwiefern sich die Wirkungen zwischen bestimmten Untergruppen (insbesondere Frauen und Männer) durch Merkmale auf der Individual- oder Unternehmensebene erklärbar sind. [...]
Additional information: Endbericht – April 2016. Forschungsprojekt im Auftrag der Deutschen Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH
Keywords: 330; Elektrizitätspolitik; Entwicklungshilfe; Elektrizitätsversorgung; Ländlicher Raum; Wirkungsanalyse; Kleinstunternehmen; Solartechnik; Herd; Kenia